Preparation of slides for the teaching and study of mitosis using selected root tips - Cadiz, Nora Iglesia- 1948- (1977)
The aim of the study was to present some suggested materials and procedures in the preparation of slides for the teaching and study of mitosis using selected root tips. The technique used in the preparation of slides is smear and squash technique as outlined by Donald Johansen in his book entitled "Plant Microtechnique." Results showed that the roots best suited for the teaching and study of mitosis are roots grown from garlic bulbs and grass. There is periodicity in the rate of mitotic activity. Further, the smear and squash technique work well with mongo, garlic, and grass but not with corn, rice, and beans.
"March, 1977."
Vita.
Thesis (M.A.T. Biology)--University of the Philippines, Diliman.
Keywords: Biology -- Study and teaching -- Philippines; Mitosis -- Slides; Slides (Photography) -- Philippines; Teaching -- Philippines -- Aids and devices